The Juridical Implications for the Cancellation of the Deed of Sale of Rights Caused Due to the Criminal Action of Fraud - Maulana, Aji (Jurnal Konstatering, 2023)
This research aims to analyze the juridical implications of canceling the deed of sale and purchase of land rights caused by criminal acts of fraud in Tegal Regency. This research is a descriptive research with a sociological approach. Data collection was carried out through interviews, literature studies and documentation studies. Data analysis was carried out in a qualitative descriptive manner. This research shows that the juridical implication of canceling the deed of sale and purchase of land rights is due to a criminal act of fraud based on the provisions of Article 1321 of the Civil Code, namely that the agreement is deemed to have never existed and can be filed for cancellation based on Article 1328 in conjunction with Article 1449 of the Civil Code. The party committing the fraud must provide compensation to the injured party in the event that the cancellation of the said sale and purchase deed causes a loss.